Study Of The Carbon Dioxide (Co2) Laser Inert Gas Cutting On Inconel 718 Using Empirical Approach And Finite Element Analysis - Nyon , Ken Yoong (2011)
Laser cutting is a thermal cutting process in which a highly intense laser beam melts the material throughout the material thickness and form a cut kerf width. In Malaysia, laser cutting become one of the most common industrial application of laser especially in sheet metal processing industries. Inconel 718 is a type of high strength nickel-based alloy, thus makes it difficult to cut using conventional cutting methods. In this research, laser inert gas cutting was identified as the best method to cut the material and nitrogen gas is chosen as the inert gas. Laser cutting of Inconel 718 for 1 mm and 2 mm thicknesses were simulated by using commercial finite element analysis (FEA) code,